Peran Orang Tua terhadap Keberhasilan Pembelajaran Anak di Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Nurul Muttaqien Desa Mandalamekar Kabupaten Bandung - Khasyanil Mudhauwamah; Rasyid, Mujahid (UNISBA Press, 2024)
Abstract. his study emphasizes the importance of parental support and involvement in enhancing the effectiveness and efficiency of children's education, particularly within the context of madrasahs and religious education. Effective communication between parents and the school is seen as a key factor in supporting the learning process and fostering the religious character of children. The research aims to investigate how education and learning processes are conducted in madrasahs, explore the role of parents in supporting the success of educational programs in madrasahs, and identify the planning, implementation, evaluation processes, as well as the supporting and inhibiting factors that influence educational success. The study uses a qualitative approach with descriptive methods, gathering data through direct observation, in-depth interviews, and document analysis. The findings reveal that parents play a crucial role in fulfilling the basic needs of children, such as financial support and balanced nutrition, which are essential for their health and development. Parents are also actively involved in supporting educational programs in madrasahs, including religious activities and Qur’an learning. Despite challenges like children’s attraction to games and technology, as well as the parents’ limited knowledge of religious education, they still recognize the importance of guiding their children in religious studies at home. Collaboration between parents and madrasahs is vital in ensuring a holistic educational experience for children. Abstrak. Penelitian ini menyoroti peran penting dukungan dan keterlibatan orang tua dalam meningkatkan efektivitas pendidikan anak di madrasah, khususnya dalam pendidikan agama. Komunikasi efektif antara orang tua dan sekolah dianggap sebagai faktor kunci dalam mendukung proses pembelajaran serta pengembangan karakter religius anak. Tujuan penelitian ini adalah meneliti pelaksanaan pendidikan di madrasah, mengeksplorasi peran orang tua dalam mendukung program pembelajaran, serta mengidentifikasi proses perencanaan, pelaksanaan, evaluasi, dan faktor pendukung atau penghambat keberhasilan pendidikan. Pendekatan kualitatif dengan metode deskriptif digunakan, dengan data dikumpulkan melalui observasi, wawancara mendalam, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa orang tua berperan dalam memenuhi kebutuhan dasar anak, seperti kebutuhan finansial dan nutrisi, yang penting untuk kesehatan dan perkembangan mereka. Orang tua juga aktif mendukung program pembelajaran di madrasah, termasuk kegiatan keagamaan dan pengajaran Al-Qur’an. Meskipun demikian, tantangan yang dihadapi meliputi ketertarikan anak pada game dan teknologi serta keterbatasan pengetahuan agama orang tua. Namun, mereka tetap berusaha mendampingi anak dalam belajar agama di rumah dan bekerja sama dengan pihak madrasah untuk meningkatkan pembelajaran agama. Kolaborasi yang baik antara orang tua dan madrasah sangat penting dalam mendukung pendidikan yang holistik bagi anak-anak.